IMPLEMENTATION OF THE FREE NUTRITIOUS MEAL POLICY IN BONDOWOSO REGENCY - Sarah Meirina Sari (Halu Oleo University, 2025)
The MBG program is part of the national strategy to address malnutrition and stunting among school-aged children. This study aims to analyse the implementation of the Free Nutritious Meal Program (MBG) policy at Kuntum Insan Cemerlang Integrated Islamic Elementary School (SDIT KIC) in Bondowoso. This research employs a descriptive qualitative approach using Edward’s policy implementation theory, which includes three dimensions: planning, implementation, and monitoring. Data were collected through in-depth interviews, observations, and document analysis, utilising source triangulation to ensure data validity. The findings reveal that the planning stage was conducted through effective coordination between the Nutritional Fulfilment Service Unit (SPPG) and the school, covering target setting, food distribution logistics, and identification of student needs. At the implementation stage, the program has operated relatively effectively, positively influencing student attendance and the cultivation of healthy habits. However, technical constraints such as limited transport capacity and food distribution schedules that are not fully aligned with the school timetable pose ongoing challenges. In terms of monitoring, while both field inspections and online evaluations are conducted, the effectiveness of oversight remains limited due to budgetary constraints and institutional capacity. This study recommends strengthening local governance mechanisms, enhancing human resource capacity, and optimising the monitoring system to ensure the sustainability and improved impact of the MBG program for students.